2019
DOI: 10.1016/j.neuropharm.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic alcohol vapor exposure on reinstatement of alcohol seeking induced by U50,488

Abstract: Alcohol dependence and stress are associated with relapse to alcohol during abstinence, but the underlying mechanisms are poorly understood. Kappa opioid receptors (KOR) are involved in alcohol reward and in the effects of stress. Previously, in non-dependent rats, we showed that KOR in the bed nucleus of the stria terminalis (BNST) mediate reinstatement of alcohol seeking induced by the selective KOR agonist U50,488. Here, we determine the effects of chronic, intermittent exposure to alcohol vapor on U50,488-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Studies using local inactivation with baclofen/muscimol support the role of a number of these sites in reinstatement induced by footshock, including the OFC, NAC core, ventral BNST, CeA, and VTA (Capriles et al, 2003; McFarland et al, 2004). This earlier work using local inactivation and our present and previous data using Fos mapping are consistent with the importance of the extended amygdala in stress-induced reinstatement (Kalivas and McFarland, 2003; Funk et al, 2016, 2019; Koob and Volkow, 2016; Lê et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Studies using local inactivation with baclofen/muscimol support the role of a number of these sites in reinstatement induced by footshock, including the OFC, NAC core, ventral BNST, CeA, and VTA (Capriles et al, 2003; McFarland et al, 2004). This earlier work using local inactivation and our present and previous data using Fos mapping are consistent with the importance of the extended amygdala in stress-induced reinstatement (Kalivas and McFarland, 2003; Funk et al, 2016, 2019; Koob and Volkow, 2016; Lê et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…See Figure 1A for experimental timeline. As in our previous publication using similar training conditions (Lê et al, 2018; Funk et al, 2019), rats demonstrated reliable alcohol self-administration (approximately 0.7 g/kg at the end of training) and comparable extinction of the alcohol-reinforced responding (Figure 1B–C).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In the central amygdala, increased levels of dynorphin release and receptor coupling have been linked to elevated alcohol consumption and negative affect following chronic alcohol exposure (Kissler et al, 2014;Kissler & Walker, 2016). Finally, blockade of KORs in the BNST reduced alcohol consumption, negative affect, and physiological withdrawal symptoms following chronic alcohol exposure (Erikson, Wei, & Walker, 2018), while activation of KORs in this region enhanced alcohol seeking following chronic alcohol exposure (Funk, Coen, Tamadon, & Le, 2019). Together, these studies clearly demonstrate that parts of the extended amygdala which regulate negative affective states and modulation of reward have disrupted KOR function following chronic alcohol exposure; however, whether similar adaptations occur in the BLA, particularly in response to exposure in adolescence, is unknown.…”
Section: Introductionmentioning
confidence: 99%